2021
DOI: 10.1080/09273948.2020.1859257
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab for the Treatment of Ocular Inflammatory Disease

Abstract: Tocilizumab (TCZ; Actemra®; Roche/Genentech in the US; Chugai Pharmaceutical Co. in Japan) is a recombinant, humanized monoclonal antibody directed against the interleukin-6 (IL-6) receptor and currently approved by the Food and Drug Administration (FDA) and the European Commission to treat adults with moderately to severely active rheumatoid arthritis (RA) and pediatric patients with polyarticular Juvenile Idiopathic Arthritis (JIA) or systemic JIA. The FDA has also approved TCZ to treat giant cell (temporal)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…Moreover, Tocilizumab seems to be a valid option in patients who have failed Abatacept as demonstrated in our cohort of patients and in those of Calvo-Rio et al ( 13 ), containing 3/8 and 6/25 patients previously treated with that drug, respectively. Moreover, in a recent revision of the literature, Cunningham et al ( 27 ) highlighted the potential use of Tocilizumab to treat ocular inflammatory disease refractory to the conventional immunosuppressive therapies, including TNF inhibitors, as second or third-line therapy, not only in adult patients but also in children. However, literature results showed that when Tocilizumab has been administered subcutaneously, it showed a decrease in activity in controlling ocular inflammation and maintaining remission ( 22 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tocilizumab seems to be a valid option in patients who have failed Abatacept as demonstrated in our cohort of patients and in those of Calvo-Rio et al ( 13 ), containing 3/8 and 6/25 patients previously treated with that drug, respectively. Moreover, in a recent revision of the literature, Cunningham et al ( 27 ) highlighted the potential use of Tocilizumab to treat ocular inflammatory disease refractory to the conventional immunosuppressive therapies, including TNF inhibitors, as second or third-line therapy, not only in adult patients but also in children. However, literature results showed that when Tocilizumab has been administered subcutaneously, it showed a decrease in activity in controlling ocular inflammation and maintaining remission ( 22 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the levels of IL-10 and IL-6 were investigated in cases suspected of having intraocular lymphoma. In addition, determining IL-6 levels in other cases of uveitis as well enables evaluation of the extent of intraocular inflammation and could thus prove beneficial in selecting treatment options such as tocilizumab [ 31 , 32 ]. Furthermore, the improvement in visual acuity is only a secondary effect.…”
Section: Discussionmentioning
confidence: 99%
“…Une étude a montré l'efficacité du tocilizumab chez des patients présentant un oedème maculaire cystoïde uvéitique réfractaire aux agents immunosuppresseurs conventionnels ou aux anti-TNF-α (39). Une autre étude a également montré, chez des patients avec uvéites réfractaires sévères, l'efficacité du tocilizumab par voie intraveineuse (40). Le tocilizumab est contre-indiqué chez les patients ayant des antécédents de cancer, de tuberculose, d'infection fongique invasive telle que la candidose, l'aspergillose et la pneumocystose, ou d'infections bactériennes, virales ou parasitaires actives (40).…”
Section: * Tocilizumabunclassified
“…Une autre étude a également montré, chez des patients avec uvéites réfractaires sévères, l'efficacité du tocilizumab par voie intraveineuse (40). Le tocilizumab est contre-indiqué chez les patients ayant des antécédents de cancer, de tuberculose, d'infection fongique invasive telle que la candidose, l'aspergillose et la pneumocystose, ou d'infections bactériennes, virales ou parasitaires actives (40). * Certolizumab pégol Le certolizumab pégol est un anticorps monoclonal dirigé contre le TNF-alpha.…”
Section: * Tocilizumabunclassified